2011
DOI: 10.1016/j.actamat.2011.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Nucleation and growth of the γ′(AlAg2) precipitate in Al–Ag(–Cu) alloys

Abstract: Precipitation of the γ ′ (AlAg 2 ) phase was investigated in Al-Ag(-Cu) alloys using high resolution transmission electron microscopy and scanning transmission electron microscopy. Precipitation commenced with segregation of silver to stacking faults, followed by thickening in steps corresponding to single unit cell ledges. In conjunction with gradual segregation of silver and aluminium into ordered layers this yielded γ ′ phase platelets with a thickness of either 2 or 3× the AlAg 2 c-lattice parameter Plates… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…An Al-1.68%Ag alloy aged at 200 • C for times varying from as-quenched to 7 days exhibits the microstructure expected from previous studies [21,60]: finely distributed Ag-enriched coherent precipitates known as GP zones and sparsely distributed γ precipitates. Fig.…”
Section: Atomic Structure: Haadf-stem Imaging Simulation and Analysissupporting
confidence: 63%
See 1 more Smart Citation
“…An Al-1.68%Ag alloy aged at 200 • C for times varying from as-quenched to 7 days exhibits the microstructure expected from previous studies [21,60]: finely distributed Ag-enriched coherent precipitates known as GP zones and sparsely distributed γ precipitates. Fig.…”
Section: Atomic Structure: Haadf-stem Imaging Simulation and Analysissupporting
confidence: 63%
“…GP zone and γ . The absence of shear in ζ minimises the energy barrier for its formation, which is considered to restrict γ nucleation [60]. Previous calculations also have shown that pure Ag layers lower the stacking fault energy in Al [70], which offers a pathway for a ζ to γ transformation.…”
Section: Discussionmentioning
confidence: 98%
“…3(a), 4(c) and 7(a)) did not show the alternating strong and weak contrast that was expected for the Ag-rich and Al-rich layers in this structure [27,28]. In an earlier report on thickening of γ ′ precipitates, we noted that Ag and Al did not appear to be ordered in single unit cell thickness γ ′ precipitates [29] and an investigation into ordering of silver in γ ′ precipitates in Al-Cu-Ag alloys is underway.…”
Section: Comparison With Other Al Alloy Systemsmentioning
confidence: 47%
“…High angle annular dark field (HAADF) / annular dark field (ADF) scanning transmission electron microscopy (STEM): (262,269,292,301,307,326,333,334,344,348,400,408).…”
Section: Energy-filtered Transmission Electron Microscopy (Eftem) / Ementioning
confidence: 99%